STRUKTUR GEOLOGI BAWAH PERMUKAAN LINTASAN PANGALENGAN-SUBANG, IMPLIKASINYA TERHADAP KESTABILAN LAHAN - Subagio Subagio; Bambang Suci Widijono (Jurnal Geologi dan Sumberdaya Mineral, 2009)
The high anomaly pattern of West Java extending from Banten Province to the boundary of West - Central Java area, changes to low anomaly pattern in Bandung to Pamanukan. This phenomenon formed anomaly alignment with high gradient in the boundary part of both anomaly patterns. The profile pattern of Bouguer anomaly along PangalenganÂSubang and Gudangkahuripan-Parongpong sections show more detailed illustration of the subsurface geology structures. Qualitative and quantitative gravity analyses that were supported by surface geological data, sediment thickness, and remote sensing data, estimate that the anomaly alignment reflects a fault that formed a big graben. The anomaly profiles also describe some fault forming some horsts and grebens. Based on erotion intensity esoect in the mountainous area, and geological structures, the land stability of this area is interpreted as very low. Keywords.' high, low, anomaly alignment, structure, Pangalengan-Subang Section, horst, graben, land stability